2012
DOI: 10.1159/000345725
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog Signaling and VACTERL Association

Abstract: Hedgehog (Hh) signaling is vital for the patterning and organogenesis of almost every system. The specificity of these developmental processes is achieved through a tight spatio-temporal regulation of Hh signaling. Mice with defective Hh signal exhibit a wide spectrum of anomalies, including Vertebral defects, Anal atresia, Cardiovascular anomalies, Tracheoesophageal fistula, Renal dysplasia, and Limb defects, that resemble strikingly the phenotypes observed in VACTERL association in humans. In this review, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 188 publications
2
27
0
1
Order By: Relevance
“…a nodular expression pattern in glomeruli). These data suggested that HHIP might delay or disorient the usual gradient SHH expression pattern establishment from distal (high) to proximal (low) [25,26], since HHIP is expressed in cells adjacent to those expressing SHH to antagonise its activity [12]. Our in vitro studies in MK4 and UB tip cells with or without high-glucose media elucidated a potential counterbalance between Hhip and Shh gene expression in both differentiated UB and MM epithelium, and hint that this interaction is critical in the nephrogenic process.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…a nodular expression pattern in glomeruli). These data suggested that HHIP might delay or disorient the usual gradient SHH expression pattern establishment from distal (high) to proximal (low) [25,26], since HHIP is expressed in cells adjacent to those expressing SHH to antagonise its activity [12]. Our in vitro studies in MK4 and UB tip cells with or without high-glucose media elucidated a potential counterbalance between Hhip and Shh gene expression in both differentiated UB and MM epithelium, and hint that this interaction is critical in the nephrogenic process.…”
Section: Discussionmentioning
confidence: 92%
“…During normal kidney development, the balance of HHIP-SHH signalling appears to be critical in the control of a series of sequential events of nephrogenic processes [25,26]. Upon high glucose insult, for example, in our murine model, the offspring of diabetic dams had a markedly different expression pattern of HHIP when compared with offspring of normal non-diabetic dams.…”
Section: Discussionmentioning
confidence: 98%
“…Reports of true familial cases of VACTERL association (≥3 component features; CFs) are rare; however, the prevalence of single CFs in relatives of patients with VACTERL association is ~10% suggesting a genetic etiology to some extent [37, 39]. The deletion of genes in the Sonic hedgehog pathway (for example SHH , GLI , and HOXD13 ) modeled in mice mimics many of the same malformations as found in VACTERL association, which have resulted in a profound interest in these genes [40]. However, only mutations of HOXD13 [41] and FOXF1 [42, 43] have been reported in humans with VACTERL association, while SHH and GLI2 mutations are associated with holoprosencephaly [40].…”
Section: Discussionmentioning
confidence: 99%
“…The deletion of genes in the Sonic hedgehog pathway (for example SHH , GLI , and HOXD13 ) modeled in mice mimics many of the same malformations as found in VACTERL association, which have resulted in a profound interest in these genes [40]. However, only mutations of HOXD13 [41] and FOXF1 [42, 43] have been reported in humans with VACTERL association, while SHH and GLI2 mutations are associated with holoprosencephaly [40]. Furthermore, mutations in ZIC3 have been reported in several cases of VACTERL association [4345].…”
Section: Discussionmentioning
confidence: 99%
“…Suppressor of Fused (Sufu) is a key negative regulator of Gli transcription factors, it reduces Gli transcriptional activity by promoting the formation of Gli3 repressor (Gli3 R ) and the cytoplasmic sequestration of Gli activators (Gli A ) 18,19 .…”
mentioning
confidence: 99%